2022
DOI: 10.1002/yea.3687
|View full text |Cite
|
Sign up to set email alerts
|

Fungal diversity on brewery filling hall surfaces and quality control samples

Abstract: Breweries produce an increasing selection of beer and nonbeer beverages. Yeast and filamentous fungi may compromise quality and safety of these products in several ways. Recent studies on fungal communities in breweries are scarce and mostly conducted with culture‐dependent methods. We explored fungal diversity in the production of alcoholic and nonalcoholic beverages in four breweries. Samples were taken for next generation sequencing (NGS) at the key contamination sites in 10 filling lines. Moreover, fungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…3.1 | Phenotypic screening of fungal brewery isolates for brewing-relevant traits A total of 56 yeast strains, previously isolated from industrial brewery environments (Sohlberg et al, 2021), were screened for various brewing-relevant phenotypes. Among the strains were 18 different species from 10 genera, and the isolation environments included brewery air, brewery surfaces, raw materials and spoiled products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3.1 | Phenotypic screening of fungal brewery isolates for brewing-relevant traits A total of 56 yeast strains, previously isolated from industrial brewery environments (Sohlberg et al, 2021), were screened for various brewing-relevant phenotypes. Among the strains were 18 different species from 10 genera, and the isolation environments included brewery air, brewery surfaces, raw materials and spoiled products.…”
Section: Resultsmentioning
confidence: 99%
“…A recent survey of the microbiota in multiple breweries yielded a large collection of fungal isolates (Sohlberg et al, 2021). While a broad microbiota may typically be seen as a negative in an industrial brewery, we wanted to turn this into a positive.…”
Section: Introductionmentioning
confidence: 99%
“…Tremellomycetes are often isolated from cereal grains such as wheat, rice, maize, and sorghum, and may be found in the mucosal surfaces of approximately 1–10% of the healthy human population (Shoff and Perfect 2021 ). However, interestingly, they have been the dominant class in some wineries and breweries (Sohlberg et al 2022 ). Groups within this class may be extremely harmful or beneficial to humans (Weiss et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this effect was also caused by "wild" yeasts that developed on the surface of hop cones, which can inhibit the development of moulds. E. Sohlberg et al (2022) showed that "wild" yeast can proliferate during the initial phases of fermentation, outnumbering other species of microorganisms, including lactic acid bacteria, which are producers of lactic acid. These results confirm the assumption made.…”
Section: Figure 6 Flow Chart Of Production Of Fermented Milk Beverage...mentioning
confidence: 99%
“…Control sample 1 (C) was already unfit for consumption on Day 6 of storage. Yeasts have a higher resistance to lactic acid than other microorganisms, which allows them to grow dominantly (Sohlberg et al, 2022). As a result, the shelf life of fermented dairy products is extended.…”
Section: Figure 6 Flow Chart Of Production Of Fermented Milk Beverage...mentioning
confidence: 99%